Visible light photo-Fenton catalytic properties of starch functionalized α-FeOOH/β-FeOOH/Cu2O p-n-p heterojunction nanostructures - Pal S.; Kumar A.; Kumar U.; Prakash R.; Sinha I. (My University, 2025)
Photocatalysts with p-n-p heterojunctions can result in efficient charge separation. This idea motivated the synthesis of starch functionalized α-FeOOH/β-FeOOH/Cu2O heterojunction nanocomposites. All components in the composite have visible range band gaps. In a step-wise procedure, Cu2O nanostructures were precipitated on starch functionalized α-FeOOH/β-FeOOH nanocomposites. Mott Schottky plots confirmed p-n-p heterojunction formation. It enhanced charge separation and slowed down recombination resulting in efficient visible-light photocatalytic activity. The activity of this photocatalyst was evaluated for the photo-Fenton degradation of p-nitrophenol (PNP) and methyl orange (MO). Both degradation reactions follow zero-order kinetics. The photocatalyst remained stable during the organic pollutant degradation process even after repeated use. © 2023 Elsevier Ltd